DIGITAL HUMANITIES AND DIGITAL KNOWLEDGE (DHDK) International second cycle/Master degree - Francesca Tomasi (Umanistica Digitale, 2018)
This contribution presents the international degree programme in Digital Humanities and Digital Knowledge. DHDK offers a cross-disciplinary curriculumdesigned to foster close connections between humanities and the sciences of modeling, representation and processing of information and knowledge.